Communicative City Features in Technopole Development: A Case Study in Bandung, Indonesia - Ridwan Sutriadi; Fajar Nurghifari Aziz; Afrizal Ramadhan (Journal of Regional and City Planning, 2022)
The ‘communicative city’ and ‘technopole’ concepts are important in current urban development strategies since they deal with optimizing information as well as improving knowledge to support the planning process. This study aimed to identify the extent to which the features of a communicative city are present in the initial development of the Gedebage Technopole area in Bandung, Indonesia. Using a qualitative research approach, we found that some communicative city characteristics, namely, community attachment, potential to create economic activities, considering culture and history, and communication patterns, are present in the development. Interactions among the development actors display a simple triple helix model, where the government, academia, and the business sector perform their respective roles. However, communication patterns and active synergies among the actors have not been created optimally to support the initial development of the Gedebage Technopole area. Recognizing the development actors are vital because the key to the success of a technopole lies in the contribution of all actors involved and the synergy between them. This will affect the existence of a multiple helix ecosystem as a sustainable regional competitiveness engine.